Design for smart maintenance enabled by BIM and IoT - Fialho, Beatriz Campos (2021)
Building Design Process management plays a strategic role in the Architecture, Engineering and Construction (AEC) industry concerned with business performance, users comfort and satisfaction, and sustainable use of natural resources over buildings lifecycles. Of particular importance are the Reactive Maintenance (RM) services performed within the longest and costly phase of Operation and Maintenance (O&M). RM is characterized by delays, waste, and difficulties in service prioritization and identification of root causes of failures, impacting on critical problems attendance and users experience. Such inefficiencies are mainly related to the management of asset information and communication and hamper the generation and access to accurate information over a lifecycle. Recently, Information and Communication Technologies (ICTs), such as Building Information Modelling (BIM) and Internet of Things (IoT) have been applied to Facilities Management (FM) activities, showing potential for predictive and sustainable practices. However, the literature lacks scientific and empirical evidence regarding process requirements and impacts involved in their implementation in FM. In this respect, this research aimed at the development of a framework for BIM and IoT implementation in reactive maintenance services oriented to a predictive approach from the definition of three key objectives: (i) to characterize critical reactive maintenance problems and scenarios and opportunities for BIM and IoT implementation; (ii) to analyse and classify BIM and IoT solutions recently applied to FM and reactive maintenance services according to their benefits, gains, enablers, and barriers; and (iii) to characterize strategies and decisions involved in the planning, development, implementation, testing, and assessment of a BIM and IoT-based smart maintenance system and its impacts on the maintenance services and potential contributions to the design phase. The research was based on a pragmatic philosophy and a qualitative and quantitative mixed method design. Multiple Case Study and Prototyping were the research strategies, adopting university campuses as objects of investigation. Literature Review and Systematic Literature Review (SLR) supported the generation of theoretical data for the multiple case study and prototyping and discussion of the findings. Documental Analysis, Semi-structured Interviews, Focus Group, and Prototype development assisted the generation of empirical data on universities FM sector and RM services. Qualitative and Content Analyses were applied to qualitative data, whereas Statistical Analysis involved quantitative ones. Both research process and methodology contributed to knowledge gain. The study has provided a holistic approach of the topic through the clarification of circumstances in which maintenance services and FM sectors can benefit from BIM and IoT and identification of technological, procedural, and policy issues involved in their implementation. The research findings have evidenced a necessity for the identification of critical services and activities within organizations and standards, guidelines, and upskilling actions for an efficient data management between BIM and IoT systems and over a buildings lifecycle. They have also demonstrated the role of building performance information as an input for improvements in O&M and the initial design process stages. The thesis has addressed an agenda towards an innovative, sustainable, and efficient management of buildings, mitigating the environmental impacts of AEC industry and its contributions to climate change.